The Debate on the Baltic Crusades and the Making of Europe - Bombi, Barbara (History compass, 2013)
The Baltic Crusades represent a long-term phenomenon that lasted for about 300 years (1147-1525). The nature of these crusades has been controversial from the very beginning, as they aimed at conquering new land, expanding and consolidating the borders of Christendom, as well as at converting the local pagan population. Along with the ethical issues that are linked to conversion by means of crusading, the debate on the Baltic Crusades has also been heavily influenced by the political situation in the Baltic region and the making of Europe in the 20th century, from German domination and the rise of National Socialism, to the Cold War and finally the independence of the Baltic republics. Two historiographical approaches are mainly addressed in this essay: on the one hand, some works have focused on the religious aspects of mission, conversion and crusading, taking into account the role of the papacy, preaching and ecclesiastical institutions; on the other hand, historians have been interested in conversion and crusading in the Baltic region as means of economic, social and political expansion that contributed to the formation of political unity in Europe during the High Middle Ages, foreshadowing to some extent the well-known events of the 20th century.